1984
DOI: 10.1093/nar/12.11.4539
|View full text |Cite
|
Sign up to set email alerts
|

Polymer support oligonucleotide synthesis XVIII1.2): use ofβ-cyanoethyi-N,N-dialkylamino-/N-morpholino phosphoramidite of deoxynucleosides for the synthesis of DNA fragments simplifying deprotection and isolation of the final product

Abstract: Various 5'O-N-protected deoxynucleoside-3'-O-beta-cyanoethyl-N,N-dialkylamino-/N- morpholinophosphoramidites were prepared from beta-cyanoethyl monochlorophosphoramidites of N,N-dimethylamine, N,N-diisopropylamine and N-morpholine. These active deoxynucleoside phosphates have successfully been used for oligodeoxynucleotide synthesis on controlled pore glass as polymer support and are very suitable for automated DNA-synthesis due to their stability in solution. The intermediate dichloro-beta- cyanoethoxyphosphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
352
0
3

Year Published

1988
1988
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(359 citation statements)
references
References 11 publications
3
352
0
3
Order By: Relevance
“…The inserts were subcloned into vectors Ml3mp18/19 or pUCl9 and sequenced according to Sanger et al [8] using uni-primer or l&mer oligonucleotide primers as indicated by blocks in fig.2. Oligonucleotides for sequencing and Northern blotting were synthesized by the phosphoamidite method [9] on an Applied Biosystems DNA synthesizer and purified by HPLC.…”
Section: Cdna Cloning and Sequencingmentioning
confidence: 99%
“…The inserts were subcloned into vectors Ml3mp18/19 or pUCl9 and sequenced according to Sanger et al [8] using uni-primer or l&mer oligonucleotide primers as indicated by blocks in fig.2. Oligonucleotides for sequencing and Northern blotting were synthesized by the phosphoamidite method [9] on an Applied Biosystems DNA synthesizer and purified by HPLC.…”
Section: Cdna Cloning and Sequencingmentioning
confidence: 99%
“…Synthesis of oligodeoxyribonucleotides Oligodeoxyribonucleotides were synthesized on an Applied Biosystems Model 380B DNA synthesizer using standard solidphase ,B-cyanoethyl phosphoramidite chemistry (26,27 on an AST Premium 386/33 computer was used to integrate the volume of each rectangle.…”
Section: Introductionmentioning
confidence: 99%
“…First, domains which are encoded by a single exon (exons 5 -7 and 16 -18), second, domains which are encoded by a set of two exons; these exons are separated by a randomly inserted intron, which is, nevertheless, always within DNA stretches which code for subdomain A (exons [8][9][10][11][12][13][14][15][19][20][21][22][23], and third, domains 13 and 14, portions of which are found in the most probably fused exon 24 (Fig. 2 B).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocols strictly followed the instructions of the manufacturers. Sequence-specific oligonucleotides used as internal sequencing primers were synthesized on a MilliGen/Biosearch 7500 DNA synthesizer [13].…”
Section: Subcloning Of 5' and 3' Genomic Clones And Dna-sequence Analmentioning
confidence: 99%